Children of the revolution : an Inspector Banks novel - Robinson, Peter, 1950- (Robinson, Peter, 1950- Inspector Banks series., 2014)
"A disgraced college lecturer is found murdered on a disused railway line near his home. He has 5,000 euros in his pocket, yet in the four years since his dismissal has been living a poverty-stricken and hermit-like existence. There are many suspects, mostly at the college where he used to teach, but Detective Chief Inspector Alan Banks, much to the chagrin of his boss, soon becomes fixated on Lady Veronica Chalmers, who appears to have links with the victim going back to the early 1970s at the University of Essex, then a hotbed of political activism. Banks suspects that Lady Chalmers is not telling the whole truth, and after he pushes his inquiries a bit too far, he is called on the carpet and warned to lay off. He must continue to conduct his investigation surreptitiously. When the breakthroughs come, they are not the ones that Banks and his team expected, and everything turns in a different direction and moves into very high gear"--